THE ROLE PLAYED BY FACEBOOK IN DEVELOPING STUDENTS’ ENGLISH LANGUAGE SKILLS - Imran Ullah (University of Chitral Journal of Linguistics and Literature, 2020)
This study investigates students’ perception about the use of Facebook as a popular forum of social media in relation to learning English as a foreign language. Their approaches while using Facebook and the nature of Facebook have also been examined. Data were collected from sixty-five undergraduate students through the tool of questionnaire. Findings suggest that Facebook use is highly effective in developing students’ different skills and areas of English language. Some of the possible threats to students’ proficiency have also been pointed out. The study concludes that students on the whole are positive about the advantages in English language learning while using Facebook. Facebook is not only use for messages, and talking but get something new for learning.